(untitled) (Dissertation Nursing, 2024)
BACKGROUND: Education in clinical settings represents a crucial step in the university process for students on degree courses in the health and medical professions. In nursing education, this is emphasised, as they have the opportunity to gain practical experience and come face-to-face with different working realities during each clinical placement. Based on these experiences, it is therefore essential to carry out a periodic evaluation of the internship settings. OBJECTIVES: The main objective of this work is to implement an evaluation tool for the clinical training environment to provide feedback concerning student placement locations and improve the quality of university clinical training. METHOD: This research study protocol describe an observational study, with formal recruitment of nursing degree courses and subsequently inclusion of students from the differemt academic years. The study involves the application of the CLES+T questionnaire in participating degree courses, initially to be able to have an overall vision and subsequently assessing its implementation as a possible permanent evaluation tool. EXPECTED RESULTS: It is expected, from the study described in this protocol, that the participating population will consider the questionnaire as a way of critically analysing the clinical environment. A broad participation of the nursing student population and good feedback of the examined environments is expected.